Is respiratory exchange ratio an alternative to estimate anaerobic threshold in trained runners? - Fernando Diefenthaeler; Raphael Luiz Sakugawa; Rodolfo André Dellagrana; Bruno Follmer; Elisa Cristina Lemos; Wagner de Campos (Universidade Federal de Santa Catarina, 2017)
Several studies showed that respiratory exchange ratio (RER) have been used as an alternative to evaluate the aerobic capacity in a single incremental test. However, few studies have investigated trained runners. The aim of this study was to verify if the respiratory exchange ratio (RER) could be used as an alternative criterion for estimating anaerobic threshold (AT) in long-distance runners. Nineteen male long-distance runners volunteered to participate in the study. An incremental treadmill test was performed with initial speed of 10 km·h-1 with increments of 1 km·h-1 every 1 min until voluntary exhaustion. The variables measured were oxygen uptake (VO2), first and second ventilatory thresholds (VT1 and VT2, respectively), intensity corresponding to RER level of 1.0 (iRER1.0), peak velocity (PV), heart rate (HR), and rate of perceived exertion (RPE). One-way repeated measure analysis variance was used, following Bonferroni post hoc test. Agreement between parameters was evaluated by Pearson correlation and dispersion error. There were no significant differences between iRER1.0 and VT2 parameters. The correlations were significant between iRER1.0 and VT2 parameters for absolute and relative VO2, speed, and HR (r=0.95; r=0.60; r=0.72; r=0.81, respectively). A small mean error (-0.2 km·h-1) was observed between iRER1.0 and VT2. However, it was also observed an overestimation trend for high speeds. In conclusion, iRER1.0 can be used as an alternative method to detect AT in long distance runners. However, its use is limited in runners with high aerobic capacity.